MONITORING OF ATOMOXETINE EFFICIENCY IN CORRECTION OF THE SCHOOL DYSADAPTATION - O.A. Sobokar'; A.S. Petrukhin (Педиатрическая фармакология)
In the given article, the authors highlight the results of the research into the school dysadaptation of the children, who have undergone intracranial vascular injuries in neonatal period. Researchers also studied the efficiency of atomoxetine for the correction of this pathology. The authors demonstrated both its high efficiency and good tolerance and safety in the event of the attention deficiency and hyperactivity disorder.Key words: school dysadaptation, attention_deficit and hyper activity disorder, treatment, children.